Antidepressants induce regionally discrete, sex-dependent changes in brain's glutamate content - Kokras, N; Antoniou, K; Polissidis, A.; Papadopoulou-Daifoti, Z. (Neurosci Lett, 2009)
Growing evidence suggests the involvement of glutamate in mood disorders and in the response to antidepressants. However, there is no information regarding a hypothesized sex-dependent glutamatergic modulation following treatment in animal models of depression. We comparatively assayed in male and female Flinders and control Sprague-Dawley rats glutamate and aspartate tissue levels in the prefrontal cortex, hippocampus and nucleus accumbens following 14-day treatment with either 10mg/kg clomipramine or mirtazapine, intraperitoneally. Clomipramine increased cortical glutamate in both sexes and hippocampal glutamate only in female Flinders rodents. Mirtazapine had no effect on cortical glutamate content but increased hippocampal glutamate in both Flinders sexes. Neither mirtazapine nor clomipramine altered glutamate levels in the nucleus accumbens. There were no any significant differences in aspartate levels. However, in control male SD rats clomipramine and mirtazapine significantly decreased cortical aspartate levels. Our results indicate that two different types of established antidepressants induce a brain region-specific effect on glutamate content. This effect is also characterized by sex-dependent differences mainly in the hippocampus, highlighting a differentiated response of glutamate to distinct antidepressants.
Keywords: Animals; Antidepressive Agents/*administration & dosage; Brain/*drug effects/*metabolism; Depression/*drug therapy/*metabolism; Female; Glutamic Acid/*metabolism; Male; Rats; Sex Factors; Tissue Distribution/drug effects